Effects of a training intervention to foster precursors of evaluativist epistemological understanding and intellectual values. (October 2015) - Hefter, Markus H.; Renkl, Alexander; Riess, Werner; Schmid, Sebastian; Fries, Stefan; Berthold, Kirsten
Abstract: Kuhn (2001) proposed two crucial prerequisites for the will to engage in argumentative thinking: Evaluativist epistemological understanding that provides the base for regarding argumentative thinking reasonable and intellectual values that reflect the extent to which people regard intellectual engagement as being worthwhile. Against this background, we developed a computer-based training intervention in the domain of ecology to foster precursors of evaluativist epistemological understanding and intellectual values as well as conceptual knowledge about epistemological understanding and intellectual values. We tested the training intervention in a control-group experimental design at two points of time: immediately after the intervention and one week later. Participants were 66 German high school students (35 female; mean age = 18.21). We found positive effects of our training intervention on epistemic orientation, intellectual values, and conceptual knowledge that were (still) observable after one week. Overall, the present computer-based training intervention can be regarded as a promising first step on the way to fostering important prerequisites of the will to engage in argumentative thinking. Highlights: We developed a training on prerequisites for the engagement in argumentative thinking. Our training fostered epistemic orientation and intellectual values. The quality of self-explanations mediated the effect on conceptual knowledge. Epistemic orientation mediated the effect of the training on intellectual values. Positive effects of our training could still be found one week later.